An analysis of soccer tournament goal attempts - Stanway, B.; Beeching, K. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: In soccer, key performance indicators have been established, these consist of shots on target, goals and total shots (Castellano et al., 2012; Lago-Penas et al., 2011; Lago-Balesteros and Lago-Penas. 2010; Luhtanen et al., 2001). Subsequently, how goals are scored or attempted and which zone the goals originate from will be analysed. Navarro ef al. (2016) suggests, research should aim to establish the efficiency and effectiveness of team possession styles, when analysing performance and subsequent outcomes (i.e. scoring probability of offensive possessions). Therefore, the aim of the study is to analyse the team possession style and its effectiveness, in tournament soccer. Methods: UEFA Champions League matches 2017-18 (n=111) and UEFA European Championships 2016 matches (n=51) will be analysed using JMP version 14 discovery software (SAS Institute. JMP Statistical Discovery. NC. USA). Data using 10 attacking variables, for the type of assist and 13 attacking variables, for the type of attempt and outcome, whilst including 18 zones of the soccer pitch (Horn ef al., 2002; Grant ef al., 1998; Williams et al., 2003). have been analysed. These were analysed in accordance to the team possession styles and transition location (Wright ef al., 2011). team possession styles include elaborate attack (Tenga ef al., 2010; Lago-Penas ef al., 2012). counter attack (Tenga ef al., 2010; Liu ef al., 2015; Lago-Penas ef al., 2012), direct play (Sgro ef al.. 2016; Lago-Penas et al., 2012). secondary goal attempt and set piece (Liu et al., 2016; Hewitt ef al., 2016). To test for changes in chance creation and goals scored for each possession style in each zone, a repeated measures design linear mixed model using Restricted Maximum Likelihood (REML) method will be used. Estimates based on the least square means will be reported alongside the standard error (SE). Results: Data is currently being collected and processed, this will be completed before 22nd July 2018. Initial exploratory findings, for location of attempt in the UEFA European Championships 2016, show significant differences between winning and losing teams, for zone 14 (p>0.05) and 17 (p>0.05). Furthermore, when analysing assist location in the UEFA Champions league 2017-18. zone 14 to zone 17 (p<0.05). zone 16 to zone 17 (p<0.05). and zone 17 to zone 17 (p<0.01), significantly differed when comparing winning to losing teams. Conclusion: Other research has shown an advantage in recovering ball possession as close to goal as possible to increase goal scoring opportunities (Garganta et al.y 1997; Larson. 2001). Shots from a counter attack, have been shown to improve the probability of winning (Liu ef al.y 201S; Tenga ef al.y 2010). In summary, using tactical modelling will provide information on performance, to enhance the understanding of coaches and performance analysts (Liu et al.y 2015).